Determinants of Islamic bank financing in Malaysia: an empirical study using linear and nonlinear ARDL model - Bakri Abdul Karim,; Zulkefly Abdul Karim,; Muhammad Hafiz Mohd Shukr, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper examines the dynamics relationship between the Islamic bank financing and selected macroeconomic variables in Malaysia using monthly data covering the period of January 2007 to June 2016. Utilizing both linear and non-linear ARDL method, the results show that there is no long-run relationship among the variables. The results also indicate that there is no presence of both long-run and short-run asymmetric effects from industrial production index and rate of financing towards Islamic bank financing. In addition, Granger-causality test also shows no causality running from these factors to Islamic bank financing. Therefore, we conclude that to some extent the Islamic bank financing is stable and resilient. Muslims customers continue to support the Islamic banking and are not profit-motivated by the substitution effect as Malaysia has dual banking system. The banking system which based on profit sharing is able to cushion the Islamic financial system from interest rate and economics fluctuation thus reducing the risk of financial volatility.